Philosophy and social uncertainty some brief reflections - Claros, Mario Germán Gil (Seven Editora, 2023)
This writing focuses attention on five major problems of the present that affect philosophy, the philosopher's discourse. This is how we see the school, the ecosystem, technology, politics linked to life, knowledge and subjectivity, become big questions for philosophy today, before addressing its future. It is thinking what is typical of philosophical thought in a social context. DOI:https://doi.org/10.56238/sevened2023.006-089